1997
DOI: 10.1161/01.atv.17.6.1185
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Platelets in Neutrophil Adhesion and Vasoconstriction After Deep Carotid Arterial Injury by Angioplasty in Pigs

Abstract: In previous studies we have shown that platelets can support neutrophil adhesion to the injured vessel wall in vitro and that neutrophils contribute to vascular tone regulation after arterial injury in vivo. In this study, we investigated the implication of platelets in neutrophil adhesion and the vasomotor response to arterial injury in vivo. 111In-labeled neutrophil adhesion and angiographic vasoconstriction were quantified after deep carotid arterial injury by balloon angioplasty in normal (n = 8), thromboc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…10 In this model, we have found that platelet depletion was associated with decreased neutrophil adhesion to damaged arterial surfaces, 11 confirming our previous findings showing increased neutrophil adhesion in the presence of platelets 12 in a concentration-dependent manner. 11 These studies provide strong evidence for platelets involvement in neutrophil adhesion to damaged arterial surfaces. The interaction between platelets and neutrophils have been shown to be dependent on P-selectin (CD62P, GMP-140, or PADGEM) expression on activated platelets.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…10 In this model, we have found that platelet depletion was associated with decreased neutrophil adhesion to damaged arterial surfaces, 11 confirming our previous findings showing increased neutrophil adhesion in the presence of platelets 12 in a concentration-dependent manner. 11 These studies provide strong evidence for platelets involvement in neutrophil adhesion to damaged arterial surfaces. The interaction between platelets and neutrophils have been shown to be dependent on P-selectin (CD62P, GMP-140, or PADGEM) expression on activated platelets.…”
supporting
confidence: 91%
“…10,11,33 The animals were sedated by intramuscular injection of 20 mg/kg ketamine and 3 mg/kg azaperone, intubated, and mechanically ventilated with O 2 /air. Anesthesia was maintained with 0.5% to 1% halothane.…”
Section: Animal Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Although well tolerated, balloon inflation causes deep arterial injury, resulting in endothelial denudation, platelet and leukocyte activation, oxidative stress, and vasoconstrictor release. 7 In a small subset of patients, this leads to adverse effects on the microvasculature, resulting in clinical events. 8 Balloon angioplasty has been shown to cause immediate and prolonged endothelial dysfunction of conduit vessels.…”
mentioning
confidence: 99%